Diagenesis and its impact on the reservoir quality of the fourth member of Xujiahe Formation, Western Sichuan Depression, China. (May 2019) - Li, Mengyao; Zhu, Rong; Lou, Zhanghua; Yin, Wei; Hu, Zongquan; Zhu, Hongquan; Jin, Aimin
Abstract: The fourth member of the Xujiahe Formation (T3 x 4 ) in the Western Sichuan Depression is typical of the tight gas sandstones of China. The member is composed of three types of sandstone: litharenite, sublitharenite, and feldspathic litharenite. Some of these sandstones contain a large proportion of carbonate rock fragments. These calcarenaceous sandstones (CCSs) can be differentiated from ordinary sandstones (OSs). The reservoir properties of the fourth member are quite poor (average porosity = 5.9%, average permeability = 1.41 mD). These properties were influenced by several diagenetic processes, including compaction, feldspar dissolution, precipitation of carbonate cements, and clay cementation. Mineral distribution patterns and quantitative data show that the authigenic quartz in T3 x 4 sandstones is mainly sourced from SeI reactions, feldspar dissolution, and kaolinite illitization. Quartz cements occupy only a small fraction of the reservoir space. Carbonate cementation (primarily calcite) is dominant in the research area. Mineral distribution patterns and isotopic composition trends suggest that the carbonate cements in the sandstones originated both inside and outside of the sandstones. Dissolution of inorganic carbonate rock fragments is the main internal carbon source of carbonate cements in CCSs. In OSs, the contribution is much smaller. Organic carbon derived from the thermal evolution of kerogen in the mudstones that migrated into sandstones via diffusion is the main carbon source in OSs. Due to a combination of compaction of ductile fragments and carbonate cementation, T3 x 4 reservoir sandstones in Western Sichuan Depression exhibit low porosities. In T3 x 4 sandstones, porosity is highest for samples where both the detrital ductile grain content and carbonate cement content are low. Highlights: Quantitative diagenesis in the T3 x 4 sandstones was examined. Sources of fluids and cementation patterns were discussed. Carbonate cement is the dominant cement, have both organic and inorganic sources. Quartz cement in sandstones with internal source reduce little porosity. Carbonate cement and high content of ductile grains are factors reduce porosity significantly.